Synthesis and selective topochemical fluorination of the cation and anion-vacancy ordered phases Ba2YCoO5 and Ba3YCo2O7.5. - Luo, K; Tran, T; Halasyamani, P; Hayward, M (2013)
The synthesis and characterization of two cation-ordered, anion-vacancy ordered phases, Ba2YCoO5 and Ba3YCo2O7.5, is described. Neutron powder diffraction data reveal both phases adopt structures in which octahedral Y(3+) and tetrahedral Co(3+) centers are ordered within a "cubic" perovskite lattice. The unusual ordered pattern adopted by the cations can be attributed to the large concentration of anion vacancies within each phase. Reaction of Ba2YCoO5 with CuF2 under flowing oxygen topochemically inserts fluorine into the host material to form Ba2YCoO5F0.42(1). In contrast Ba2YCoO5 does not intercalate oxygen, even under high oxygen pressure. The selective insertion of fluorine, but not oxygen, into Ba2YCoO5 is discussed and rationalized on the basis of the lattice strain of the resulting oxidized materials. Magnetization and neutron diffraction data reveal Ba3YCo2O7.5 and Ba2YCoO5F0.42 adopt antiferromagnetically ordered states at low-temperature, while in contrast Ba2YCoO5 shows no sign of long-range magnetic order.